1984
DOI: 10.1007/bf02619607
|View full text |Cite
|
Sign up to set email alerts
|

Culture conditions induce the appearance of immortalized C3H mouse cell lines

Abstract: Mouse fibroblasts were cultured by three different procedures: (a) changing the 0.2 ml/cm2 of growth medium every 2nd d and seeding 1 X 10(5) cells/cm2 after confluency; (b) changing the 0.4 ml/cm2 of growth medium only at subculture performed at confluency by a 1:2 split and keeping the bottles incubated on a rocking platform; (c) the same as Method b but keeping the bottles stationary throughout culture. By Method a no lines were immortalized over 36 experiments whereas Method b gave 1/4 immortalized lines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Rare cells grow past this barrier, termed crisis, to form p e r m a n e n t cell lines that are capable of growing in culture indefinitely. Rodent cells have proven to be the m o s t amenable to the study of this process because they immortalize in culture efficiently and spontaneously (Todaro and Green 1963;Meek et al 1977;Curatolo et al 1984). This is in contrast to normal h u m a n and avian primary fibroblasts, which have not been observed to i m m o r t a l i z e spontaneously in culture (Hayflick 1965;Smith and PereiraSmith 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rare cells grow past this barrier, termed crisis, to form p e r m a n e n t cell lines that are capable of growing in culture indefinitely. Rodent cells have proven to be the m o s t amenable to the study of this process because they immortalize in culture efficiently and spontaneously (Todaro and Green 1963;Meek et al 1977;Curatolo et al 1984). This is in contrast to normal h u m a n and avian primary fibroblasts, which have not been observed to i m m o r t a l i z e spontaneously in culture (Hayflick 1965;Smith and PereiraSmith 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency at which cells escape senescence appears to be species dependent. Whereas rodent cells have been observed to undergo spontaneous immortalization quite efficiently (Todaro and Green 1963;Meek et al 1977;Curatolo et al 1984), normal human and avian cells have rarely, if ever, been shown to be capable of spontaneous immortalization (Hayflick 1965;Smith and Pereira-Smith 1990).…”
mentioning
confidence: 99%
“…At present, the reports on malignant transformation of cultured human cells in vitro are rare (6-9,12,13), while malignant transformation in vitro could be observed in embryonic cells from mice (14)(15)(16). One hypothesis to explain this phenomenon is that the number of mutational events required to confer immortality on rodent cells is fewer than the number required for human and avian cells (or the rates of mutation are different) (17).…”
Section: Discussionmentioning
confidence: 99%
“…At the first passage, cells were grown in 25-cm2 plastic flasks (Corning, France) as follows: the culture medium (0.4 ml/cm2) was renewed only at subculture, cells were split 1:2 at confluency, which is defined as a decrease in mitotic index [Curatolo et al, 1984], This culture procedure gave rise to three immortalized sister pop ulations from the parental line, namely A, B and C. The three immortalized lines appeared during the late 'phase three' (i.e. the last phase of a normal life span).…”
Section: Cells and Culture Methodsmentioning
confidence: 99%
“…In a previous study we found that slight differences in culture procedures produce different effects on normal C3H mouse em bryo cells, determining the success of 'spon taneous' immortalization and transforma tion [Curatolo et al, 1984], In view of the reproducibility of our culture method for in ducing immortalization (which was achieved in about 85% of the cell populations studied [Curatolo et al, 1984], this study was under taken to characterize three transformed lines derived from a C3H normal embryo fibro blastic primary culture [Curatolo et al, 1980].…”
Section: Introductionmentioning
confidence: 99%